Computational quest to inhibit enoyl-acyl carrier protein reductase (InhA) enzyme in Mycobacterium tuberculosis from Lannea coromandelica (Houtt.) Merr. metabolite via molecular docking and dynamics - Muhammad Askar (Pensoft Publishers, 2024)
This research is a computational exploration to look for natural compounds that can inhibit enoyl-acyl carrier protein reductase (InhA) enzyme from Mycobacterium tuberculosis (MTB). One of Indonesia's native plants that has been reported to inhibit InhA from MTB is the Lannea coromandelica (Houtt.) Merr., known to contain various active metabolites. However, the molecular activity of the metabolites has not been determined. The aim of this research is the discovery and testing computationally of the binding of metabolites from Lannea coromandelica (Houtt.) Merr. The metabolite ligands are obtained from the natural compound database KNApSAcK, and the 3D structure of the receptor is obtained from the PDB website with the code 1BVR. Subsequently, molecular docking is performed using MGL Tools v.1.5.6 and AutoDock Tools v.4.2.3 software. High-performance computers are used for molecular dynamics simulations with the Gromacs 2016.3 software for a duration of 100 nanoseconds (ns). The docking simulation results show that metabolites show a negative binding energy and close to the value of the native ligand. Moreover, molecular dynamics simulation analysis revealed significant stability of the C1436 ((2R,3R)-3-Hydroxy-5,7,4'-trimethoxyflavanone)-InhA complex over 100 nanoseconds. Molecular dynamics simulations demonstrate that from MM-PBSA value compound C1436 showed MMPBSA binding energy −104.995 kJ/mol, closely approaching the value of the native ligand, which is −142.999 kJ/mol. Furthermore, from the molecular dynamics simulation analysis, C1436 compound demonstrates stability very similar to the native ligand, as observed from the RMSD, RMSF, Rg, RDF, SASA, and PCA analysis. In conclusion, the compound from Lannea coromandelica (Houtt.) Merr. has the potential to serve as a lead compound for inhibiting InhA in MTB.